2015
DOI: 10.5301/uro.5000115
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilations: Genito-Urinary Complications and Ethical-Legal Aspects

Abstract: Many women in the world are still undergoing female genital mutilations (FGMs) even if in almost all the countries, the practice of FGM is illegal. The increase of immigration, particularly from African Countries, to Europe, and Italy too, led to consider this phenomenon with particular attention and skill. All the operators in health services need to know the different types of FGMs and the related complications and the psychological and sexual sequels. Urological complications, in particular, are not rare an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…As defined by World Health Organization gender violence is 'the greatest public health issue and violation of human rights in the world; it is a violation of a person's physical and mental integrity (WHO 2014). SA is a traumatic life event in which the negative outcomes increase with increasing severity of abuse including physical maltreatment (McCauley et al 1997) such us lacerations, fractures, genital mutilation, sexually transmitted diseases (Lacey 1990), gynecologic disorders (Walling et al 1994;Golding et al 1998) unwanted or pathological pregnancies (Murphy et al 2001), depression (Wise et al 2001), eating disorders (Goodwin et al 2003), self-destructive behaviours (Alix et al 2017) genito-urinary and sexual disorders (Vella et al 2015), post-traumatic stress disorders (Kendler et al 2000;MacMillan et al 2001;Sprinter et al 2007;Jonas et al 2011;Gauthier-Duchesne et al 2017;Bottomley et al 1999). Internationally, different approaches are taken to the collection of forensic evidence and to the clinical and psychological assessment of alleged victims Berry et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As defined by World Health Organization gender violence is 'the greatest public health issue and violation of human rights in the world; it is a violation of a person's physical and mental integrity (WHO 2014). SA is a traumatic life event in which the negative outcomes increase with increasing severity of abuse including physical maltreatment (McCauley et al 1997) such us lacerations, fractures, genital mutilation, sexually transmitted diseases (Lacey 1990), gynecologic disorders (Walling et al 1994;Golding et al 1998) unwanted or pathological pregnancies (Murphy et al 2001), depression (Wise et al 2001), eating disorders (Goodwin et al 2003), self-destructive behaviours (Alix et al 2017) genito-urinary and sexual disorders (Vella et al 2015), post-traumatic stress disorders (Kendler et al 2000;MacMillan et al 2001;Sprinter et al 2007;Jonas et al 2011;Gauthier-Duchesne et al 2017;Bottomley et al 1999). Internationally, different approaches are taken to the collection of forensic evidence and to the clinical and psychological assessment of alleged victims Berry et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The genitourinary complications of FGM were reviewed by Vella et al in 2015 5 . Some studies suggested that in women with the consequences of FGM, there is an important role for reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that in women with the consequences of FGM, there is an important role for reconstructive surgery. 5 The aim is to restore normal anatomy and offer the potential for improved female sexuality 5. The same review demonstrated that reconstructive surgery after FGM is associated with reduced pain and restored pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…This argument is strongly denied by medical classification of the WHO that named "mutilation" as all forms of female circumcision and consequently no far similarities must be drawn between two practices. Thus, the practices banned by the WHO, as female genital mutilations, even with patient consent, could not be considered lawful [43].…”
Section: Ethical and Legal Arguments Of Male Circumcision 61 Adultsmentioning
confidence: 99%